(untitled) (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2023)
Every area of life, including the learning process, has been impacted by the growth of the 21st-century world, which is characterized by the use of information and communication technology in all facets of daily life. Every field of work requires changes in competence and skills as a result of developments. Critical thinking, problem-solving, and teamwork are crucial skills for success in the twenty-first century. Schools must be equipped to prepare kids for life in the twenty-first century. The goal of all teaching and learning activities in schools must be to prepare students with the skills needed for the twenty-first century. The capacity for learning expands and becomes resourceful. Because of advancements made in the 21st century, learning has become more dynamic. The educational system must therefore be able to address all of the difficulties and skill requirements of the 21st century. As a result, education must plan out its educational programs through the curriculum that pupils will be taught. The curriculum is everything that pupils will learn in order to accomplish a particular objective. To accommodate all available skills and obstacles, curriculum changes are implemented. Responding to the demands of the twenty-first century presents exceedingly complicated issues for the curriculum. The curriculum is modified appropriately to meet these requirements and challenges. The actual challenge is staying on course with the vision, mission, and goals of national education. Consequently, a curriculum that can both internally and externally address the needs of the 21st century is required.